Exploration of the multi-scenario spatiotemporal evolution, trade-off and synergy relationships, and driving factors of ecosystem services in Henan Province, China, under the background of land use change - Sun, Yanchao; Qi, Menghao; Wang, Weiye; Cai, Jun; Tian, Fengya (Frontiers in Ecology and Evolution, 2025)
IntroductionEcosystem services (ESs) assessment plays a significant role in managing ecological resources. From the perspective of land use, this research aims to uncover the complex interdependence between ESs and their key drivers to clarify and optimize the ecological function zoning in the region.MethodsThis research focuses on Henan Province in China, quantifying five key ESs, namely, carbon storage (CS), habitat quality (HQ), soil conservation (SC), water conservation (WC), and water yield (WY), and assessing their interactions from 2000 to 2020 and in 2035. Moreover, this study explores the social - ecological driving factors influencing these ESs. Finally, it classifies five types of ecosystem service bundles (ESBs).Results(1) From 2000 to 2020, the land use evolution was characterized by a large expansion of construction land, a continuous decrease in cultivated land area, and relatively stable changes in other land types. In the ecological protection (EP) scenario of 2035, the cultivated land area decreased the most, and the forest land area increased slightly. CS and HQ showed a trend of degradation, while SC, WY, and WC first fluctuated and then increased. (2) The synergistic relationship between each function was the main one, among which WC-WY, CS-HQ and HQ-SC showed significant synergistic relationships, CS-WC and HQ-WC showed a change from trade-off to synergistic relationship, while CS-WC and HQ-WC were mainly trade-off relationships. Meanwhile, most of the B4 bundles in the central part of the region were dominated, and the rest of the service bundles showed a decrease in volatility. (3) Elevation and slope are the dominant factors restricting the spatiotemporal distribution of CS, HQ, and SC. Temperature and precipitation are the primary conditions affecting the spatiotemporal differentiation of WY and WC. Moreover, the interaction between topographic factors and climatic conditions has a greater impact on each function than a single factor.DiscussionIn conclusion, during the study period from 2000 to 2020, there was a significant spatio-temporal heterogeneity in various ecosystem service functions in Henan Province. Approaches such as exploring the trade-off and synergistic relationships of different ecosystems in 2035, classifying ecosystem service clusters, and discussing potential driving factors can provide references for the territorial space governance and ecological environment protection in Henan Province.